The adaptor ASC exacerbates lethal Listeria monocytogenes infection by mediating IL‐18 production in an inflammasome‐dependent and ‐independent manner. Issue 12 (22nd October 2014) - Tsuchiya, Kohsuke; Hara, Hideki; Fang, Rendong; Hernandez‐Cuellar, Eduardo; Sakai, Shunsuke; Daim, Sylvia; Chen, Xi; Dewamitta, Sita R.; Qu, Huixin; Mitsuyama, Masao; Kawamura, Ikuo
Abstract : Listeria monocytogenes induces the formation of inflammasomes and subsequent caspase‐1 activation, and the adaptor apoptosis‐associated speck‐like protein containing a CARD (ASC) is crucial for this response. However, the role of ASC in L. monocytogenes infection in vivo is unclear. In this study, we demonstrate that ASC has a detrimental effect on host defense against L. monocytogenes infection at a lethal dose (10 6 CFU), but not at a sublethal dose (10 3 CFU). During lethal L. monocytogenes infection, serum levels of IL‐18 and IL‐10 were markedly elevated in WT mice, but not in ASC KO mice. IL‐18 KO mice were more resistant to lethal L. monocytogenes infection than WT mice and had lower levels of serum IL‐10. Furthermore, blockade of IL‐10 receptor resulted in a reduction in bacterial counts, suggesting that ASC and IL‐18 might exacerbate L. monocytogenes infection through induction of IL‐10. We noticed that maturation of IL‐18 during lethal infection was partially independent of caspase‐1, but was critically dependent on ASC. ASC was required for the elevation of serum neutrophil serine protease activity, which correlated with caspase‐1‐independent IL‐18 maturation and IL‐10 production. Collectively, these results suggest that ASC plays a detrimental role in lethal L. monocytogenes infection through IL‐18 production in an inflammasome‐dependent and ‐independent manner.